THE IMPACT OF LIQUIDITY, PROFITABILITY, AND ACTIVITY ON SHARES RETURN WITH DIVIDEND POLICY AS CONTROLLING VARIABLE - Hastuti, Rini Tri; Andrew, Richard; P., M. Bintang (Graduate Program of Universitas Tarumanagara, 2023)
This study was conducted to examine the impact of liquidity, profitability and activity variables on shares returns which can be controlled by dividend policy. This study uses secondary data with a population of financial report data published on capital market. The sample taken is only the issuers of manufacturing companies. The data obtained were 52 issuers using purposive sampling method. Statistic application programs are programs used in processing and analyzing data. The final conclusion of this study shows that the liquidity and activity variables have an impact on shares returns, while the profitability variable has no impact on shares returns. The test by including the controlling variable Dividend policy concluded that the controlling variable was not able to moderate the relationship between liquidity, profitability, and activity on shares returns.